Design and Development of a Maternal and Infant Care Service Management Information System for MomCha Babycare - Ilham Hashfy Fahrezy; Deni Sutaji (Cattleya Darmaya Fortuna, 2026)
MomCha Babycare is a maternal and infant care service provider in Surabaya. Its manual business processes cause recording errors and reporting difficulties. This research aims to design and implement a web-based Management Information System (MIS) for MomCha Babycare. The development method uses the Waterfall SDLC consisting of five phases: requirement analysis, design, implementation, testing, and maintenance. The system was built using Next.js and React for the admin side, Node.js with the Express framework on the backend, MySQL as the database, and Midtrans as the payment gateway. The resulting system covers authentication, service, customer, order, payment, and reporting modules. Testing was conducted through black-box testing and User Acceptance Test. All black-box test scenarios returned valid results, and UAT obtained an average score of 4.64 out of 5, categorized as Very Good. This MIS supports the digitalization of MomCha Babycare's business processes, making service management more efficient and accurate.